2021
DOI: 10.2106/jbjs.20.01585
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Diseases Increase the Risk of Periprosthetic Joint Infection

Abstract: Background: A large body of evidence is emerging to implicate that dysregulation of the gut microbiome (dysbiosis) increases the risk of surgical site infections. Gut dysbiosis is known to occur in patients with inflammatory bowel disease (IBD), allowing for translocation of bacteria across the inflamed and highly permeable intestinal mucosal wall. The null hypothesis was that IBD was not associated with an increased risk of periprosthetic joint infection (PJI) after primary total hip and knee arthroplasty.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…Six studies collected data from nationwide administrative databases, 5,18,19,[21][22][23] and two from a single-centre hospital database. 20,24 Five studies reported mixed cohorts of patients suffering from IBD 5,[19][20][21]24 and three included patients with CD only. 18,22,23 One study investigated hip, knee, and shoulder arthroplasty, 21 two investigated hip and knee arthroplasty, 5,24 two investigated total knee arthroplasty only, 22,23 and three investigated total hip arthroplasty only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies collected data from nationwide administrative databases, 5,18,19,[21][22][23] and two from a single-centre hospital database. 20,24 Five studies reported mixed cohorts of patients suffering from IBD 5,[19][20][21]24 and three included patients with CD only. 18,22,23 One study investigated hip, knee, and shoulder arthroplasty, 21 two investigated hip and knee arthroplasty, 5,24 two investigated total knee arthroplasty only, 22,23 and three investigated total hip arthroplasty only.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Recently, several studies have been published investigating the potential impact of IBD on postoperative outcomes in patients undergoing joint arthroplasty. 5,[18][19][20][21][22][23][24][25] These studies produced conflicting results, making it essential to take an evidence-based approach to synthesize the cohort data and draw more concrete conclusions in the context of modern surgical practice. To the best of our knowledge, no systematic review or meta-analysis has been performed to date to evaluate the impact of coexisting IBD on the clinical outcomes in joint arthroplasty patients.…”
Section: Introductionmentioning
confidence: 99%
“…A disruption of this link can lead to the generation of many known chronic diseases [34e36]. Interestingly, patients with an established chronic gut disease, like Crohn's and Ulcerative Colitis, are at much higher risk of PJI and other infections [37]. The increased risk of these patients for infection was not just related to the administration of immunosuppressive drugs but the actual disease itself [38].…”
Section: Discussionmentioning
confidence: 99%
“…For the best results, this interdisciplinary approach is essential. Regarding the pathophysiology, diagnosis, classification, and therapeutic strategy for PJI, we offer a perspective on current management methods in this review article [4][5][6] . Arthroplasties on the hip and knee are effective elective surgical procedures, with a 10-year survival rate of more than 95%.…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative and coagulase-negative staphylococci infections were less common, according to researchers from other studies. Up to 23% of Enterococci species and up to 46.7% of S aureus strains in the USA are vancomycin-resistant [8] . Nearly 9% of Enterococci spp.…”
Section: Introductionmentioning
confidence: 99%